INVENTARISASI JAMUR MAKROSKOPIS DI HUTAN LINDUNG BUKIT PENINTIN KABUPATEN MELAWI - Desinta Ayu Widyastuti (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2022)
A B S T R A C TMacroscopic mushrooms research in this study aims to find the types of macroscopic mushrooms found in the protected forest of bukit penintin melawi regency. Based on the results of the inventory conducted there are as many as 53 types of macroscopic fungi from 19 familles found to come from 2 many as 5 types of 2 famillies namely the family Sarcoscyphaceae and family Xylariaceae while from the phyllum Basidiomycota found as many 17 famillies with the most found namely in the family Polyporaceae ass many as 12 types while the least is the family Clavariaceae, Schizophyllaceae, Ganodermataceae, Meripilaceae, Meruliaceae, Dacrymycataceae, and Lyophyllaceae which each found only 1 type of macroscopic fungus. It is known that mushrooms are found to have the potential as food ingredients, drugs, as dekomposer and have dangerous toxic content. Kata Kunci: Macroscopic mushrooms, Ascomycota, Basidiomycota,